Growth and Antibiotic Sensitivity Status of Bacillus spp. associated with Abalone (Haliotis asinina) as Probiotic Candidate Selection - Faturrahman Faturrahman; Nurul Zulfa Fitriana; Sarkono Sarkono; Ernin Hidayati (Journal of Science and Science Education, 2023)
The use of probiotics is an innovation in an effort to increase production and fight pathogens in aquaculture cultivation environments. Probiotic candidate microorganisms are selected selectively to ensure that the probiotics used are safe and provide benefits for the host and the environment. This study aims to select probiotic candidates based on the aspects of growth and sensitivity to antibiotics from 4 isolates of Bacillus from abalone (Haliotis asinina). Growth observations were carried out by turbidimetric method using a spectrophotometer at a wavelength of 600 nm in SWC media, and antibiotic sensitivity was tested using Rifampicin, Gentamicin, Kanamycin, and Erythromycin antibiotics using the well-diffusion agar method. The growth analysis of isolates was described by a growth curve based on the OD value, and antibiotic susceptibility based on the diameter of the inhibition zone. The results showed that the growth of the four isolates of Bacillus spp. had a short lag phase, ranging from 1-2 hours, an exponential phase ranging from 15 hours to B. pumilus SLK1 and B. licheniformis SLK2 isolates, and 12 hours to B. coagulans CaK1 and B. coagulans CaK6 isolates. Antibiotic sensitivity showed that B. coagulans CaK1 isolates were sensitive to all the tested antibiotics, while B. pumilus SLK1 isolates, B. licheniformis SLK2, and B. coagulans CaK6 were only sensitive to Rifampicin and Gentamicin antibiotics. The ideal probiotic candidate is an isolate with good growth and does not have resistance properties, based on the results of this study CaK1 isolate has the potential as a probiotic candidate